Actomyosin contraction during cellularization is regulated in part by Src64 control of Actin 5C protein levels. Issue 6 (11th April 2019) - Carter, Tammy Y.; Gadwala, Swetha; Chougule, Ashish B.; Bui, Anh P. N.; Sanders, Alex C.; Chaerkady, Raghothama; Cormier, Nathaly; Cole, Robert N.; Thomas, Jeffrey H.
Summary: Src64 is required for actomyosin contraction during cellularization of the Drosophila embryonic blastoderm. The mechanism of actomyosin ring constriction is poorly understood even though a number of cytoskeletal regulators have been implicated in the assembly, organization, and contraction of these microfilament rings. How these cytoskeletal processes are regulated during development is even less well understood. To investigate the role of Src64 as an upstream regulator of actomyosin contraction, we conducted a proteomics screen to identify proteins whose expression levels are controlled by src64 . Global levels of actin are reduced in src64 mutant embryos. Furthermore, we show that reduction of the actin isoform Actin 5C causes defects in actomyosin contraction during cellularization similar to those caused by src64 mutation, indicating that a relatively high level of Actin 5C is required for normal actomyosin contraction and furrow canal structure. However, reduction of Actin 5C levels only slows down actomyosin ring constriction rather than preventing it, suggesting that src64 acts not only to modulate actin levels, but also to regulate the actomyosin cytoskeleton by other means.